Pelatihan Menggunakan Media Bola Terrhadap Kecepatan Reaksi Penjaga Gawang Olahraga Hoki - Ariq Naufal; Nina Sutresna; Ucup Yusup (Jurnal Kepelatihan Olahraga, 2021)
The aim of this study was to determine the effect of training methods on the speed reaction of hockey's goalkeeper. According to the movements, a hockey's goalkeeper athlete must have good and precise abilities to withstand shots from opposing players, of course, with speed reaction. This method of this study is using experimental method. This research was conducted at UKM Hoki UPI Bandung involving 7 people using saturated sample sampling technique. The research design was used the pre-test post-test control group. The instrument was used "the Whole Body Reaction Time Test". The author provides treatment using ball for the media, tennis court balls and reaction balls which will be compared with a control group that was not given treatment but still practiced using hockey balls. The analysis t-score using the Paired Samples t-test and the Independent Samples t-test, it can be concluded that there is a difference in the effect of increasing training using ball and hockey ball media on the speed reaction of hockey's goalkeeper.